Prevalence of diabetes and determinants: evidence from a minority region in People’s Republic of China - Chen Q; Yi Y; Xia N; Li C; Luo Z; Huang G; Chen Y; Li S; Lai L; Wang M; Tan J; Zhang J; et al. (Dove Medical Press, 2016)
Qingyun Chen,1 Yanhua Yi,2 Ning Xia,1 Chunling Li,3 Zuojie Luo,1 Gaoming Huang,3 Ying Chen,1 Shumin Li,4 Luhua Lai,1 Mingdeng Wang,5 Jing Tan,6 Jie Zhang,1 Hanlei Shen,1 Bixun Li,7 Feiqun Su,8 Hua Wei,5 Xia Dai,1 Fengji Lu,9 Shuilian Li8 1Department of Endocrinology, First Affiliated Hospital of Guangxi Medical University, 2School for International Education, Guangxi Medical University, Nanning, 3Department of Public Health, Guangxi Medical University, Nanning, 4The Second People’s Hospital of Qinzhou, Qinzhou, 5Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, 6Nandan County People’s Hospital, Nandan, 7Tumor Hospital of Guangxi Zhuang Autonomous Region, Nanning, 8Hezhou City People’s Hospital, Hezhou, 9Long’an County People’s Hospital, Nanning, Guangxi, People’s Republic of China Background: This study aimed to examine the prevalence of diabetes mellitus and other categories of glucose intolerance (impaired glucose tolerance and impaired fasting glucose) and explore the risk factors in an ethnic minority region, Guangxi Zhuang Autonomous Region, People’s Republic of China. Methods: A population-based study enrolled 53,270 residents older than 5 years in Guangxi, People’s Republic of China. The prevalence of diabetes was calculated using the 1999 World Health Organization (WHO) oral glucose tolerance test diagnostic criteria. Results: Among 53,270 individuals, the prevalence of diabetes, impaired glucose tolerance, and impaired fasting glucose was 5.96%, 7.36%, and 2.62%, respectively. Of the 3,173 individuals with diabetes mellitus, 696 (21.94%) were found to have a history of diabetes and 2,477 (78.06%) were newly diagnosed. A lower prevalence was found in Zhuang ethnic minority people compared with the majority of Han people. The prevalence was significantly associated with age, body mass index, waist-to-hip ratio, dyslipidemia, medical history of hypertension, and family history of diabetes. Conclusion: Guangxi shows a rapidly rising prevalence of diabetes. Weight control and blood lipid control are important to decrease the rapidly increasing prevalence of diabetes in Guangxi, an ethnic minority region. Keywords: diabetes mellitus, ethnic minority, OGTT, diagnosis, factors, prevalence